Pengaruh Persepsi Keseriusan dan Kemungkinan Mengambil Tindakan terhadap Pemanfaatan Layanan VCT pada Lelaki Seks Lelaki di Puskesmas Padang Bulan Kota Medan - Faija Sihombing; Roikestina Silaban; Elvipson Sinaga; Tulus JT Panjaitan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Utilization of VCT services in Male Sex Men at Padang Bulan Medan Public Health Center Pematangsiantar City is still relatively low (34.4%). The low utilization of VCT services in Male Sex Men is related to the perception of seriousness and the possibility of taking action. This study aims to analyze the influence of perceptions of seriousness and the possibility of taking action on the use of VCT services in Male Sex Men at Padang Bulan Medan Health Center Pematangsiantar City Year 2018. The type of this research is analytic research using cross sectional design. The population in this study is all MSM who utilize VCT service at Padang Bulan Medan Public Health Center Pematangsiantar City in the year 2017 that as many as 189 people and sample counted 61 people. Data were obtained by questionnaire and observation interviews, analyzed by Multiple Logistic Regression statistic test at α = 5%. The results showed that the perception of seriousness and the possibility of taking action had an effect on the utilization of VCT service to MSM in Puskesmas Padang Bulan Kota Medan and the most dominant variable influencing the use of VCT service on Male Sex Men at Padang Bulan Medan Public Health Center Pematangsiantar City was the possibility variable to take action with Exp B = 11,450 . It is suggested to health workers to increase the extension to the MSM on the use of VCT services so that MSM will come to utilize VCT services to Kota Pemassiya Kota Pemassiantar Health Office to further improve the implementation and socialization to LSL (Male Sex Man) in Pematangsiantar City about the importance of VCT service utilization and to LSL (Male Sex Men) in Padang Bulan Medan Health Center Pematangsiantar City should routinely make use of VCT services.